Knowledge Management Value Creation Through Organizational Learning - North, Klaus (Springer Texts in Business and Economics,, 2018)
This textbook on knowledge management draws on the authors' more than twenty years of research, teaching and consulting experience. The first edition of this book brought together European, Asian and American perspectives on knowledge-based value creation; this second edition features substantial updates to all chapters, reflecting the implications of the digital transformation on knowledge work and knowledge management. It also addresses three new topics: the impact of knowledge management practices on performance; knowledge management in the public sector; and an introduction to ISO 9001:2015 as an implementation framework. The book is intended not only for academic education but also as an essential guide for managers, consultants, trainers, coaches, and all those engaged in business, public administration or non-profit work who are interested in learning about organizations in a knowledge economy. Given its wealth of case studies, examples, questions, exercises and easy-to-use knowledge management tools, it offers a true compendium for learning about and implementing knowledge management initiatives.